PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), RETURN ON EQUITY (ROE), PRICE EARNING RATIO (PER), DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2011 - Purnamasari, Khairani; Dp, Emrinaldi Nur; Satriawan, Raja Adri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to test the effect of financial ratios, i.e. liquidity ratio (current ratio), leverage ratio (debt to equity ratio), and market value ratio (price earning ratio and earning per share) to total return at property companies listed in BEI. The population of this research are all property and real estate companies listed in Bursa Efek Indonesia (BEI). The samples are 35 property and real estate companies listed in BEI during the year 2009-2011. The samples are chosen by using purposive sampling method. The data are analysed with multiple regression by means of SPSS ver 17.0. The results indicate that current ratio, debt to equity ratio, and price earning ratio have influence toward to total return. Conversely return on equity and earning per share does not have influence towards total return.Keywords : Current Ratio, Debt to Equity Ratio, Return On Equity, Price Earning Ratio, Earning Per Share, Return Saham